Innovative potential of Croatian enterprises in wood processing and furniture manufacturing - Denis Jelačić (University of Zagreb, Faculty of Forestry and Wood Technology, 2008)
This paper presents the results of surveys of innovation potential conducted at wood processing and furniture manufacturing enterprises in the Republic of Croatia. The survey was conducted at 30 Croatian enterprises by using a questionnaire containing 89 questions divided in 14 major groups. The survey results showed some differentapproaches and a different current situation in Croatian enterprises. Different results were achieved in small, medium and large enterprises, but total results are below the average mark 3 (good), which can not be satisfactory. Since innovations can be considered as one of the most important factors for competitiveness of Croatian wood processing and furniture manufacturing enterprises on the European and global market, it is obvious that a lot of effort isrequired for making changes that are necessary in order to increase the competitiveness of our enterprises.